2016
DOI: 10.1038/ncomms11541
|View full text |Cite
|
Sign up to set email alerts
|

Experimental priming of encephalitogenic Th1/Th17 cells requires pertussis toxin-driven IL-1β production by myeloid cells

Abstract: CD4+ Th17 are heterogeneous in terms of cytokine production and capacity to initiate autoimmune diseases, such as experimental autoimmune encephalomyelitis (EAE). Here we demonstrate that experimental priming of encephalitogenic Th cells expressing RORγt and T-bet and producing IL-17A, IFN-γ and GM-CSF but not IL-10 (Th1/Th17), is dependent on the presence of pertussis toxin (PTX) at the time of immunization. PTX induces early production of IL-1β by CD11b+CCR2+Gr1+ myeloid cells, which are rapidly recruited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 65 publications
(76 reference statements)
6
80
0
Order By: Relevance
“…These authors also found that transmigration through the blood-spinal cord barrier triggered pro-IL-1β expression by neutrophils, and that at day seven after EAE induction, IL-1β-producing neutrophils were found in the blood. We and others also found IL-1β-producing myeloid cells in peripheral lymphoid organs at days five through eight following EAE induction (31, 32, 36, 62). These reports collectively identified a population of CD11b + Ly6C mid-hi MHC II lo-hi monocyte-derived DC/macrophages (moDCs/Macs) as the main source of IL-1β in draining lymph nodes (DLNs), and showed that these cells increase dramatically following MOG 35-55 /CFA immunization given with PTX coadjuvant.…”
Section: Cellular Sources Of Il-1β In Eaesupporting
confidence: 73%
See 3 more Smart Citations
“…These authors also found that transmigration through the blood-spinal cord barrier triggered pro-IL-1β expression by neutrophils, and that at day seven after EAE induction, IL-1β-producing neutrophils were found in the blood. We and others also found IL-1β-producing myeloid cells in peripheral lymphoid organs at days five through eight following EAE induction (31, 32, 36, 62). These reports collectively identified a population of CD11b + Ly6C mid-hi MHC II lo-hi monocyte-derived DC/macrophages (moDCs/Macs) as the main source of IL-1β in draining lymph nodes (DLNs), and showed that these cells increase dramatically following MOG 35-55 /CFA immunization given with PTX coadjuvant.…”
Section: Cellular Sources Of Il-1β In Eaesupporting
confidence: 73%
“…For this reason, the remainder of this review will focus on IL-1β, although whether IL-1α plays any role in MS remains an open question. Consistent with a critical requirement for IL-1β for EAE susceptibility, mice deficient in the inflammasome components NLRP3 (3741), ASC (36, 39, 42), caspase 1 (42, 43), and caspase 11 (44) were also at least partially resistant to EAE, as were mice treated with inhibitors of NLRP3 (45, 46) or caspase 1 (47). It is worth noting that in some reports (4042), mice immunized with larger amounts of heat-killed Mycobacterium tuberculosis ( Mtb ) (usually greater than 300 micrograms per mouse) as part of the MOG 35-55 /CFA emulsion developed an NLPR3- and ASC-independent form of aggressive EAE.…”
Section: Established Associations Between Il-1 and Autoimmune Neuroinmentioning
confidence: 67%
See 2 more Smart Citations
“…the development of encephalitogenic T cells [53]. In future studies it might also be interesting to investigate the putative effects of PTx on the c-Jun- N -terminal kinase (JNK) pathway.…”
Section: Discussionmentioning
confidence: 99%